The The Effect of Acetobacter xylinum Starter in Waste Liquid Pineapple Peel on the Properties of Nata de Pina (International Journal of Ecophysiology, 2020)
Abstract. Fresh pineapple waste consisted of saccharides, water, protein, lipid, vitamin and minerals that can be used by beneficiary microorganisms for production another food products. The aim of this study was to  investigate physical properties nata de pina made from waste liquid pineapple peel  using various  starter concentrations and length of fermentation of Acetobacter xylinum. The starter used were 20, 30 and 40% ml. Each 200 mL fresh waste containing the starter was  incubated for 14, 21 and 28 days at 29Â°C. Nata properties such as yield, thickness, fibre and water content were determined. Results showed starter concentration and length of fermentation affect and significantly (P